Spectrophotometric Determination of Mesalazine, Carbamazepine and Diclofenac Sodium in Pharmaceutical Preparations by Using Nile Blue Dye - Abdussamed Saeed; Elham Salih (College of Education for Pure Sciences, 2019)
A simple and accurate spectrophotometric method has been suggested for the determination of Mesalazine (MES), carbamazepine (CAM) and diclofenac sodium (DFS) in pure and pharmaceutical dosages. The method is based on the oxidation of drugs in acidic medium with known excess of N-bromosuccinimide (in case of MES), or bromate-bromide mixture (in case of CAM and DCF) and subsequent determination of unreacted oxidant by decolorization of nile blue dye (NB) and measure the absorbance of unoxidized dye at 640 nm. Calibration curves of the dye in the presence of studied drugs were rectilinear over the ranges 0.1-2.2, 0.4-2.4 and 0.6-2.8 µg ml-1 with molar absorptivity of 6.21×104, 1.05×105 and 1.21×105 l.mol-1.cm-1 for MES, CAM and DCF respectively. The common excipients and additives didn't interfere in their determination. The suggested method was successfully applied for determination of the studied drugs in their pharmaceutical forms resulted in a good agreement with standard British pharmacopeia method and standard addition procedure.